Effect of pulmonary rehabilitation on exhaled nitric oxide in patients with chronic obstructive pulmonary disease. Issue 7 (1st July 2001) - Clini, E; Bianchi, L; Foglio, K; Porta, R; Vitacca, M; Ambrosino, N
Abstract : BACKGROUND: In patients with mild to moderate chronic obstructive pulmonary disease (COPD) the exercise induced increase in exhaled nitric oxide (eNO) parallels that observed in normal untrained subjects. There is no information on the effects of the level of exercise tolerance on eNO in these patients. The aim of this study was to evaluate the effect of a pulmonary rehabilitation programme including exercise training on eNO in patients with COPD. METHODS: In 14 consecutive male patients with stable COPD of mean (SD) age 64 (9) years and forced expiratory volume in one second (FEV1 ) 55 (14)% predicted, fractional eNO concentration (Feno ), peak work rate (Wpeak) and oxygen uptake (V˙o 2 peak) were assessed at baseline (T–1), at the end of a 1 month run in period (T0), and after an 8 week outpatient multidisciplinary pulmonary rehabilitation programme (T1) including cycloergometer training. RESULTS: Feno did not significantly differ at T–1 and T0 (mean (SE) 4.3 (0.6) and 4.4 (0.6) ppb, respectively), whereas it rose significantly at T1 to 6.4 (0.7) ppb (p<0.02). Compared with T0, both Wpeak andV˙o 2 were significantly (p<0.05) increased at T1 (mean (SE) Wpeak from 89 (5.6) W to 109 (6.9) W);V˙o 2 peak from 1.27 (0.1) l/min to 1.48 (0.1) l/min). A significant correlation was found between baseline FEV1 and the change in Feno following the rehabilitation programme ( r =–0.71; p<0.05) and between changes in Feno and Wpeak from T0 to T1( r =0.60; p<0.05). CONCLUSIONS: Pulmonary rehabilitation in patients with mild to moderate COPD is associated with an increase in exhaled nitric oxide.